Izbira predmetov pri maturi in splošni uspeh - ali naravoslovne predmete izberejo po uspehu boljši? - Zupanc, Darko (Šolsko polje, 2010)
The European Council adopted guidelines to Member States: the total number ofgraduates in mathematics, science and technology in the EU should increase at least for 15 % from 2000 to 2010. In Slovenia, the proportion of such graduates increased only 8.3 % by the year 2006 or about 1% per year, which puts us on the last place in the EU. Access to university studies in Slovenia is granted through successfully completed Gimnazija with general Matura as fi nal examinations. In the last decade the number of general Matura graduates increased and the proportion of selected science subjects declined until 2004,thereaft er the trend is reversed. Research questions can be posed. Are candidates who select science optional subjects higher achievers in the Gimnazija prior to the Matura? Are they higher overall achievers in the fi ve subject Matura exam? ALA Tool, developed in The National Examinations Centre makes it possible to analyse studentsć selection of diff erent optional subjects and to compare grades in one subject with overall achievement. Mann-Whitney-Wilcoxon (MWW) U-test and the area above/below the Ordinal Domninance (OD) Graph were used as a measure of the dissimilarity between two overall achievement distributions of those who selected science or social science optional subjects. Th e discussion refl ects on the causes and proposed changes in the Slovenian education, on the equalization diffi culty of the science and social science subjects and on the increase of data driven effectiveness and improvement.
Keywords: (ne)naravoslovni predmeti; (social) science subjects; ALA tool; directed dissimilarity; distribution dissimilarity; educational effectiveness; gimnazija; graf ordinalne dominantnosti; grammar school; indeks; index; invisible pedagogy; izbirnost predmetov; nevidna pedagogika; optional subjects; Ordinal Dominance (OD) Graph; orodje za analize izkazanega znanja ob zaključku srednje šole; overall achievement; različnost porazdelitev; splošni učni uspeh; učinkovitost v edukaciji; usmerjena različnost; vzgoja in izobraževanje